Varied Incident Rates of Global Maritime Piracy: Toward a Model for State Policy Change - Regan, Joshua (International criminal justice review, 2022)
Maritime piracy is a problem that plagues our navigable seas. This study provides a quantitative understanding of factors that influence the frequency of yearly maritime piracy occurrences. Using a nonprobability sampling technique, 11 countries with reported cases of maritime piracy were purposefully selected. Open sourced data from the National Geospatial Intelligence Agency, the World Bank, the United Nations, the National Consortium for the Study of Terrorism and Responses to Terrorism, and the Center for Systemic Peace were utilized in this study. Using regression features, as well as socioeconomic and geopolitical data from these countries over a longitudinal period of 34 years (1985–2018), a time-series cross-sectional design provides an in-depth understanding of factors that affect the frequency of piracy occurrences. The four-factor model concluded that state weakness, total population size, gross domestic product, and total fish catch tonnage are found to be associated with the frequency of pirating activity worldwide. Policy implications and measures to mitigate piracy are also discussed.